A Review: Buildings Energy Savings - Lighting Systems Performance - Al-Ghaili A.M.; Kasim H.; Al-Hada N.M.; Othman M.; Saleh M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buildings; Digital libraries; Lighting; Lighting fixtures; Systems analysis; Cited papers; Energy efficient systems; Energy informatics; In-buildings; Information and Communication Technologies; Lighting systems; Review papers; Smart lightings; Energy efficiency